Effectiveness of an electronic health system−based best-practice advisory to enhance the time to de-escalation of vancomycin for respiratory indications - Amanda C. Gibbs; Daniel A. Jackson; Senka Runjaic; Vanessa J. Toncray; Wendelyn Bosch; Julio C. Mendez; Kevin L. Epps (Cambridge University Press, 2022)
Abstract Objective: Methicillin-resistant Staphylococcus aureus (MRSA) infection is highly unlikely when nasal-swab results are negative. We evaluated the impact of an electronic prompt regarding MRSA nasal screening on the length of vancomycin therapy for respiratory indications. Design: Retrospective, single-center cohort study. Setting: Tertiary-care academic medical center (Mayo Clinic) in Jacksonville, Florida. Patients: Eligible patients received empiric treatment with vancomycin for suspected or confirmed respiratory infections from January through April 2019 (preimplementation cohort) and from October 2019 through January 2020 (postimplementation cohort). Intervention: The electronic health system software was modified to provide a best-practice advisory (BPA) prompt to the pharmacist upon order verification of vancomycin for patients with suspected or confirmed respiratory indications. Pharmacists were prompted to order a MRSA nasal swab if it was not already ordered by the provider. Methods: We reviewed patient records to determine the time from vancomycin prescription to de-escalation. The secondary end point was incidence of acute kidney injury. Results: The study included 120 patients (preimplementation, n = 61; postimplementation, n = 59). Median time to de-escalation was significantly shorter for the postimplementation cohort: 76 hours (interquartile range [IQR], 52-109) versus 42 hours (IQR, 37-61; P = .002). Acute kidney injury occurred in 11 patients (18%) in the preimplementation cohort and in 3 patients (5%) in the postimplementation cohort (P = .01; number needed to treat, 8). Conclusions: Implementation of a BPA notification for MRSA nasal screening helped decrease the time to de-escalation of vancomycin.